2020
DOI: 10.1177/1559827620904868
|View full text |Cite
|
Sign up to set email alerts
|

Building a Thriving Lifestyle Medicine Practice Within a Primary Care Clinic: A Model for Aspiring Lifestyle Medicine Practitioners

Abstract: The field of Lifestyle Medicine (LM) is growing rapidly as individuals and communities seek real solutions to the hardship of chronic disease. Providers across various medical specialties and allied health professions are gaining certification in this field, and yet are struggling with implementation. Time constraints, concern about reimbursement, and lack of clinical experience in counseling patients are often cited as obstacles. This article will address these issues and demonstrate how LM can be successfull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Primary care clinics are a leading provider for management services of chronic noncommunicable diseases where these clinics should be equipped to provide healthy lifestyle counselling to the patients. [ 27 ] This signifies the importance of adherence of PHC physicians to a healthy lifestyle in order to ensure the effective motivation of their patients to adhere to a healthier lifestyle. This study aimed to measure the lifestyles of PHC physicians in the Jazan region, southwest of Saudi Arabia, and identify the prevalence of diabetes, hypertension, hypercholesterolemia, and obesity among this sample of physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Primary care clinics are a leading provider for management services of chronic noncommunicable diseases where these clinics should be equipped to provide healthy lifestyle counselling to the patients. [ 27 ] This signifies the importance of adherence of PHC physicians to a healthy lifestyle in order to ensure the effective motivation of their patients to adhere to a healthier lifestyle. This study aimed to measure the lifestyles of PHC physicians in the Jazan region, southwest of Saudi Arabia, and identify the prevalence of diabetes, hypertension, hypercholesterolemia, and obesity among this sample of physicians.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study among peripheral artery disease patients in NAMCS and NHAMCS found only 22% of visits involved exercise or diet lifestyle counseling . Decreasing time slots for patient encounters, as well as lack of adequate clinical training in nutrition and physical activity counselling and behavior change has been identified as barriers in primary care setting and may explain low use . More programs that focus on physician education in applying guidelines to patients, electronic medical record reminders, and assessing patient resistance routinely at office visits could help mitigate some of the barriers in increasing use of secondary ASCVD preventive therapy …”
Section: Discussionmentioning
confidence: 99%
“…In lifestyle medicine, we know that sustainable financial compensation models are essential to the growth of the field. 4,31 Building from our understanding of the value of team meetings, we advocate that interprofessional team meetings should become a standard "We're getting patients to reduce BMI to where they can actually have their [joint replacement] surgery. That's affecting our partners in orthopedic surgery… They're gaining… a patient they would have normally not have been able to do surgery on."…”
Section: Discussionmentioning
confidence: 99%
“…To address this challenge, some lifestyle medicine clinicians use a multidisciplinary approach in which they harness a strong referral network of clinicians in other disciplines to facilitate patients in making a lifestyle change. [4][5][6] However, in this multidisciplinary care model, clinicians still draw on their own discipline-specific expertise and essentially "stay within their boundaries." 7 In contrast, interdisciplinary care is a model in which clinicians "analyze, synthesize, and harmonize links between disciplines into a coordinated and coherent whole."…”
Section: Introductionmentioning
confidence: 99%